Significant spike in excess mortality in England in winter 2014/15 – influenza the likely culprit. Issue 9 (10th May 2018) - Pebody, R. G.; Green, H. K.; Warburton, F.; Sinnathamby, M.; Ellis, J.; Mølbak, K.; Nielsen, J.; de Lusignan, S.; Andrews, N.
Abstract: Significant increases in excess all-cause mortality, particularly in the elderly, were observed during the winter of 2014/15 in England. With influenza A(H3N2) the dominant circulating influenza A subtype, this paper determines the contribution of influenza to this excess controlling for weather. A standardised multivariable Poisson regression model was employed with weekly all-cause deaths the dependent variable for the period 2008–2015. Adjusting for extreme temperature, a total of 26 542 (95% CI 25 301–27 804) deaths in 65+ and 1942 (95% CI 1834–2052) in 15–64-year-olds were associated with influenza from week 40, 2014 to week 20, 2015. This is compatible with the circulation of influenza A(H3N2). It is the largest estimated number of influenza-related deaths in England since prior to 2008/09. The findings highlight the potential health impact of influenza and the important role of the annual influenza vaccination programme that is required to protect the population including the elderly, who are vulnerable to a severe outcome.